Prevalence and determinants of apparent treatment-resistant hypertension among patients in South African primary care: a single-centre observational study - Kellicia Courtney Govender; Mergan Naidoo (BMC Cardiovascular Disorders)
Abstract Introduction The surge in cardiovascular disease across Sub-Saharan Africa is largely driven by hypertension along with other cardiometabolic risk factors. South Africa, like other low-middle-income countries, faces a disproportionate burden due to the increasing prevalence of hypertension, exacerbated by low awareness, treatment, and control rates. Treatment-resistant hypertension (TRH) is a complex clinical entity and poses significant obstacles to achieving therapeutic goals. The prevalence of TRH in South Africa and its associated factors remain underexplored despite its significant cardiovascular and economic burden. Accordingly, we aimed to evaluate the prevalence, clinical and biochemical profiles, and therapeutic patterns associated with TRH among hypertensives in primary care. Methods An observational analytical study was conducted at a district hospital in KwaZulu-Natal, South Africa, from March to April 2024. Data from 400 systematically randomised hypertensive patients aged > 30 years were analysed. Participants underwent automated office blood pressure monitoring, anthropometric assessments and completed structured interviews on health behaviours and medication adherence. Clinical parameters and antihypertensive medication profiles were reviewed. Determinants of apparent TRH were identified using multivariate logistic regression. Results The mean age of the participants was 64.4 years (SD = 10.8), with a female preponderance (n = 260,65%), and nearly two-thirds comprised of Black Africans (35.3%) and Indians (30.5%). The prevalence of apparent TRH was 18.8%, comprising 11% uncontrolled and 7.8% controlled TRH. Factors significantly associated with TRH included Black African ethnicity (Odds Ratio (OR) = 2.33, p < 0.001), waist circumference (OR = 1.03, p < 0.001), left ventricular hypertrophy (OR = 3.57, p < 0.001), chronic kidney disease (OR = 3.12, p < 0.001), and dyslipidaemia (OR = 2.46, p = 0.039). Mineralocorticoid receptor antagonists were underused (10.8%). Conclusion This first report of apparent TRH prevalence in South African primary care underscores its complex association with cardiometabolic risk factors and the disproportionate burden among Black Africans. These findings highlight the urgent need for targeted, multifaceted interventions and the development of locally relevant TRH-specific guidelines to mitigate cardiovascular risks among this high-risk population.